Editorial (American Journal of Islam and Society, 2003)
It is with a deep sense of humility that I take on the responsibility of editing the American Journal of Islamic Social Sciences (AJISS), a journal established in 1984 to promote Islamically oriented scholarship in the social sciences. Now in its twentieth year, the journal has provided scholars with a forum for exploring and debating issues and concerns from diverse Muslim (or Muslim sympathetic) perspectives. It is a privilege to join the list of eminent scholars who have overseen the production of AJISS over these years - most recently, Louay Safi, a scholar with profound insight into both the Islamic and the western worlds. His is a hard act to follow. May Allah guide me. Budgetary constraints have forced AJISS to combine this year's last two issues (summer/fall 2003) into one - albeit a rather expanded volume. We hope that this is only a temporary measure, and that AJlSS will return soon to publishing four volumes a year. Of course, the articles and reviews themselves still represent the high-quality scholarship we have come to expect from contributors to AJlSS. Though not specifically theme-based, an underlying theme does unify the articles in this issue: the ongoing dialogue between Muslims and the West over issues having to do with Islam's encounter with modernity. Each article examines some aspect of this encounter: Necva Kazimov looks at the relationship between various reforms made to Egypt's divorce law and that country's reservations to the Convention on the Elimination of Discrimination Against Women (CEDA W), Fathi Malkawi analyzes the role and future needs of educating Muslim children in the United States, and Mohamad Fauzan Noordin discusses why wisdom has to be a priority in implementing and using information and communication technology (ICT). Then, lmad-ad-Dean Ahmad analyzes constitutionalism from the comparative perspective of the American Constitution and the Prophet's (peace be upon him) Madinah Covenant, Glenn E. Perry looks at the relationship between sovereignty and law in the democracy-Islam compatibility debate, and lastly, Pernille Ironside draws our attention to the Shari'ah penal law in northern Nigeria and its relationship to Nigeria's secular-based system of law ...